Durability of crosslinked polydimethylsyloxanes: the case of composite insulators - Delor-Jestin, Florence; Tomer, Namrata S.; Singh, Raj Pal; Lacoste, Jacques (Science and Technology of Advanced Materials, 2008)
Most applications of silicones are linked to their hydrophobic properties and (or) their high resistance to ageing (e. g. thermal ageing and photoageing). However, when placed in extreme environments, these materials can fail as in the case of epoxy/fiber glass composite powerlines insulators, where crosslinked polymethylsyloxanes (PDMSs) are used as the protective envelope (housing) of the insulator. We report on the behavior of both pure/noncrosslinked PDMSs and typical formulations used in industrial insulators, i.e. containing peroxide crosslinked PDMS, alumina trioxide hydrated (ATH) and silica. Special attention is paid on both (i) the sources of potential degradation and (ii) the best analytical methods that can be applied to the study of very complex formulations. (i) Aside from conventional types of ageing such as photo-ageing and thermal, hydrolytic, and service life ageings, treatments with acidic vapors, plasma and ozone possibly generating species from the reaction of a high electric field with air were also performed, which allowed to accelerate electrical and out-door ageings and to obtain differently aged materials. (ii) Aside from conventional analytical methods of polymer degradation such as FTIR/ATR spectroscopy and SEC, TG, hardness measurements, more specific methods like photo/DSC, TG/IR, thermoporosimetry, resistivity and density measurements were also performed to characterize the chemical and physical evolutions of polymer materials. In particular, it was found that treatment with nitric acid vapor has detrimental effects on the properties of both fire retardants (e. g. ATH) and PDMSs, affecting the hardness and resistivity of the formulated material.
Keywords: composite insulators; durability; PDMS; post-crosslinking; silicone